Algorithm for searching the normal mode of the power system during power reduction at power plants operating on renewable energy sources - Khudayarov, Muzaffar; Normamatov, Nuriddin; Qobulov , Shuhratbek (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: nowadays, renewable energy sources are an integral part of electric power systems. However, the variability of the operation mode of these sources poses a serious threat to the stability and reliability of power systems. Sudden decrease in generation during operation is a phenomenon that is common and leads to serious problems related to power system management. Sudden reduction in generation can be caused by various reasons such as changing climatic factors, technical failure, natural disasters and others. These situations not only cause economic losses but also cause social and environmental problems. Therefore, the development of efficient algorithms for finding the normal operation regime for the tasks of operational control of electric power systems is highly relevant. Aim: the aim of this paper is to develop an efficient algorithm to restore the normal mode of the electric power system in case of a sudden decrease in the generation of renewable energy plants. Methods: algorithm and program for searching the normal mode of an electric power system in case of sudden generation reduction, where the following methods are used: methods of steady-state calculation (in particular, Newton-Raphson method); methods of comparative analysis, methods and means of modeling of electric systems (DIgSILENT PowerFactory 2022); methods and means of data processing (Python 3.8). Results: the main result of the presented algorithm is the efficiency of finding the normal state in case of sudden generation decrease. Approbation of the algorithm was carried out on the test 14 node IEEE circuit.